Falling Into the Same Hole: Leaving Cigarette, Approaching E-Cigarette - Sheila Jessica Claudia; Ratu Mega; Lola Delvira (Borong Newinera Publisher, 2024)
Effective communication regarding the risks associated with electronic cigarettes is a crucial part of efforts to control their usage, and incorporating elements of fear is an effective method to achieve proper regulation. This research, utilizing content analysis methodology, examined three online news articles from Indonesian news portals: Kompas.com, IDNTimes.com, and Detik.com. The study aimed to describe how online news conveys the dangers of using electronic cigarettes using the Extended Parallel Process Model (EPPM). The research method employed was content analysis. EPPM explains how people manage the fear evoked by threat messages. There are two key factors that can explain how individuals respond to fear messages. The first factor is the perception of threat, consisting of the severity and vulnerability to the threat. The second factor is the perception of efficacy, consisting of response efficacy and self-efficacy. The research findings indicate that online news coverage prioritizes the perception of threat. Conversely, the aspect of efficacy perception still needs to be applied in reporting the dangers of electronic cigarettes. These results are also influenced by ethical codes, journalistic principles, and cultural influences.